1992
DOI: 10.2527/1992.7061708x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and treatment biases in estimation of carcass lean of swine

Abstract: Carcasses of 181 barrows, representing five genotypes, 1) H x HD, 2) SYN, 3) HD x L[YD], 4) L x YD, and 5) Y x L (H = Hampshire, D = Duroc, SYN = synthetic terminal sire line, L = Landrace, and Y = Yorkshire), and two levels of ractopamine (RAC) treatment (0 and 20 ppm) were completely dissected and the data were used to examine genotype and treatment (RAC) biases in estimation of fat-standardized lean weight and to evaluate accuracies and precisions realized by use of equations based on variables derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 0 publications
3
37
0
1
Order By: Relevance
“…Equations 1131 and [141 show inclusion of probe longissimus muscle depth as nonsignificant. The use of single point estimators for either percentage or weight of carcass lean were subject to prediction bias based on carcass lean and fat distribution (Gu et al, 1992). Although the data indicate a high correlation between probe-derived fat depth and ruler-derived fat depth, the fact remains that there is a low correlation between actual fat depth and total weight of dissected tissue.…”
Section: Discussionmentioning
confidence: 93%
“…Equations 1131 and [141 show inclusion of probe longissimus muscle depth as nonsignificant. The use of single point estimators for either percentage or weight of carcass lean were subject to prediction bias based on carcass lean and fat distribution (Gu et al, 1992). Although the data indicate a high correlation between probe-derived fat depth and ruler-derived fat depth, the fact remains that there is a low correlation between actual fat depth and total weight of dissected tissue.…”
Section: Discussionmentioning
confidence: 93%
“…The equations developed in this study are based on one genotype, and, given the diversity in carcass composition observed in the range of U.S. swine breeds and lines (NPPC, 1995) and the potential for genotype and treatment biases from using prediction equations (Gu et al, 1992), care must be taken when extending the use of these equations to other situations. Gu et al (1992) reported that even though dissected ham lean weight was the most accurate single measurement for predicting carcass lean content, significant genetic bias was still evident from the use of equations based on ham lean. In the present study, the loin composition measurements were more accurate than those from the ham; however, this approach needs to be extended across a wider range of genotypes and treatments to investigate biases associated with prediction equations based on the loin and other cuts.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the animal type bias found in the relationships between the reference method and the on-line instrumental methods (e.g. fat and muscle thickness measurements) seems to be a more serious problem (Branscheid, Komender, Oster, Sack, & Fewson, 1987;Engel, Buist, Font i Furnols, & Lambooij, 2004;Evans & Kempster, 1979;Gu et al, 1992;Planella & Cook, 1991;Wood & Robinson, 1989;Zelenák et al, 2004).…”
Section: Discussionmentioning
confidence: 97%